Sistemas de medição fasorial sincronizada: aplicações para melhoria da operação de sistemas elétricos de potência. - Sonia Ribeiro Campos Andrade (2008)
This master thesis investigates the application of the Synchronized Phasor Measurement Systems in Power System monitoring and control processes. The use of this technology may result in a significant improvement of electrical system operation activities. However, the consideration of synchronous phasors data in operation analyses requires new investigations and research. The present work intends to contribute to this area, by preparing a basic text designed to facilitate the initial studies concerning this field. The already existing applications of phasor measurement systems are discussed and also their theoretical fundamentals. The work also presents specific proposals related to thepractical implementation of these systems. Examples of the application of the proposals are included.